Effect of Integrated Nutrient Management on Tuber Yield and Quality and Nutrient Uptake in Coleus forskohlii Briq. - Ravikumar, M.; Venkatesha, J.; Niranjana, K. S.; Gurumurthy, B. R. (JOURNAL OF ROOT CROPS, 2013)
A field experiment was conducted at Arabhavi located in the Western dry zone of Karnataka on a clay loam soil during kharif seasons of 2006 and 2007 to study the effect of biofertilizers in combination with organic manures and inorganic fertilizers on dry matter production, tuber yield and quality, nutrient uptake and economics in coleus (Coleus forskohlii Briq.) (cv. K-8). Recommended dose of FYM @ 15 t ha-1 and NPK @ 40:60:50 kg ha-1 along with 10 kg ha-1 each of Azotobacter crucocum, Bacillus megateruim (phosphorus solubilising bacteria) and Glomus fasciculatum (vesicular arbuscular mycorrhiza) produced significantly higher dry weight of leaves (70.21 g), stem (138.38 g), tuber (39.39 g), total dry weight (247.98 g) per plant, leaf dry matter (15.00%), stem dry matter (16.97%), tuber dry matter (14.02%), forskolin content (0.76%), uptake of N (115.83 kg ha-1), P (49.59 kg ha-1) and K (151.55 kg ha-1), net returns (Rs. 39065 ha-1) and B:C ratio (1.95).